Concern Audit in Independent Auditor's Report During the Covid-19 Pandemic - Nugrahanti, Trinandari Prasetyo; Ashari, Hasan (International Journal of Scientific Research and Management (IJSRM), 2023)
This study aims to find out how the auditor's attention to the company's financial statements is reflected in the independent auditor's report (LAI) during the Covid-19 pandemic in Indonesia. This research is qualitative research using descriptive methods. The primary data source in this study was obtained through the 2020 issuer's annual report published on the Indonesia Stock Exchange (IDX) website. The population in this study are companies listed on the Stock Exchange, with a sample of 100 companies taken at random. This study concludes that most of the companies obtained a fair audit opinion without modification (WTP), as many as 83 companies. While the audit concerns opinions other than WTP, there are several records, including business continuity due to business losses resulting in a deficit in the entity, inadequate presentation and disclosure, accounting implications, and indications of earnings management. The audit concern in the independent auditor's report in this study has proven that the Covid-19 pandemic has had a major impact on the survival of companies in Indonesia, sequentially the most affected are the transportation, property, restaurant, hotel & tourism sub-sectors. ; tourism, investment companies, and building construction companies